2021
DOI: 10.1155/2021/5587848
|View full text |Cite
|
Sign up to set email alerts
|

Antiobesity and Antidiabetic Effects of Portulaca oleracea Powder Intake in High-Fat Diet-Induced Obese C57BL/6 Mice

Abstract: This study investigated the hypothesis that Portulaca oleracea L. exerts antiobesity and antidiabetic effects by evaluating blood lipid profiles, blood glucose control factors, protein expression of lipid metabolism, and insulin sensitivity improvement. Three groups of high-fat diet (HFD) induced obese C57BL/6 mice (n = 8) received treatment with low (5%; HFD + PO5%) or high (10%; HFD + PO10%) concentrations of P. oleracea powder for 12 weeks or no treatment (HFD) and were compared with each other and a fourth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…A similar pattern was observed in the HFD-treated mice. After HFD feeding for 12 weeks, the blood glucose and serum insulin concentrations were 130-160 mg/dL and 27-39 μU/mL, respectively [32][33][34]. In this study, the Lep KO and HFD-treated mice were used to compare the phenotypes of constipation.…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern was observed in the HFD-treated mice. After HFD feeding for 12 weeks, the blood glucose and serum insulin concentrations were 130-160 mg/dL and 27-39 μU/mL, respectively [32][33][34]. In this study, the Lep KO and HFD-treated mice were used to compare the phenotypes of constipation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these antioxidant compounds can also maintain the organ health due to their antimetabolic activity. 22,27,43 The presence of antioxidants in P. olaracea is associated with cellular oxidative stress. Oxidative stress is caused by reactive oxygen species that trigger cell and tissue damage, especially liver tissue.…”
Section: Pathogenesis and Pathophysiology Of Metabolic Syndromementioning
confidence: 99%
“…18,50 Moreover, purslane extract is known to inhibit reactive oxygen species; decrease adipogenic activity involving the protein PPAR-γ, C/EBPα, FABP4, FATP1 and ACS1, and also acts as an anti-inflammatory agent by reducing TNF-α (tumor necrosis factor α). 3,18,43 As a result, there was a decrease in TC, TG, LDL-C (low density lipoprotein-cholesterol), VLDL-C (very low density lipoproteincholesterol), LPO (lipid peroxidation), AI (anthrogenic index), CRF (cardiac risk factor), CRI (coronary risk index), GOT (glutamateoxaloacetate transaminase), GPT (glutamate pyruvate transaminase), GSH (glutathione), HOMA-IR (homeostatic model assessment of insulin resistance), FBS (fasting blood sugar), and QUICKI (quantitative insulin sensitivity check index) compared with untreated obese mice. 7,22,43,44 Concurrently with this decrease, there was an increase in HDL-C (high density lipoprotein-cholesterol) which resulted in a decrease in body fat and weight loss.…”
Section: Pathogenesis and Pathophysiology Of Metabolic Syndromementioning
confidence: 99%
“…Besides, P. oleracea also provides nutritional benefits due to its rich omega-3 fatty acids and antioxidant properties. 7 Modern pharmacological studies have shown that P. oleracea possesses a variety of bioactivities, including antibacterial, 8 antiulcerogenic, anti-inflammatory, 9 antioxidant, 10 neuroprotective, 11 antidiabetic, 12 antioxidant, 13 anticancer, 14 antimicrobial, 15 antiinflammatory, 16,17 antiulcerogenic, 18 hepatoprotective activity, 19 and wound-healing 20 properties. Besides, there are many compounds, including flavonoids, alkaloids, fatty acids, terpenoids, polysaccharides, vitamins, sterols, proteins and minerals, that have been isolated from P. oleracea.…”
Section: Introductionmentioning
confidence: 99%